Website-Based Sports Training Management Information System at Sport 5 Indonesia Learning Center - Putri Eka Sevtiyuni; Muklis Febriadi; Pacu Putra; Nabila Rizky Oktadini; Allsela Meriza (Universitas PGRI Palembang, 2023)
The development of technology and information at this time, makes humans very easy to get information. The ease of information that can be accessed through the internet network, encourages various institutions to be able to compete in presenting complete, interesting and reliable information. The website is one of the information media used by institutions or organizations to provide information and services. Website-Based Sports Training Management Information System at Sport 5 Indonesia Training Center is a system that is planned to be used to manage and organize sports training at Sport 5 Indonesia Training Center efficiently and effectively using website technology. In this study, the data source used was by using primary and secondary data. This primary data is used to answer researchers' questions and make decisions. While secondary data is used to complete the information needed in this study. The system approach method used is an object-oriented system approach, the object-oriented system approach method is a software development strategy that groups software as a collection of objects containing operations and data. The system development method that researchers use is to use the prototype method, The general purpose for software is not to identify detailed input, processing, or output needs. The website in the Sports Training Management Information System has been designed to help improve the efficiency, effectiveness, and attractiveness of sports training / seminars and strengthen the reputation of sports training institutions in this case Sprot 5 Indonesia Training Center